Expression of recombinant thermostable W200R protease in Pichia pastoris - Mohamad Sultan, Muhamad Zarir (2011)
Thermostable enzymes are needed in industry because of their stability in harsh industrial processes. As such there is a constant need for new inexpensive thermostable enzymes. Yeast is considered as a good host for large scale protein expression. A thermophilic Bacillus stearothermophilus F1 was found to produce an thermostable serine protease. Gene encoding pro-mature thermostable W200R protease was cloned into Pichia pastoris expression vector and placed under the control of the methanol inducible alcohol oxidase (AOX) promoter. The recombinant pPICZαB/W200R protease gene was transformed into E. coli for plasmid replication before subsequent transformation into P.pastoris strain X-33, GS115 and SMD1168.This expression system efficiently secreted W200R protease into the culture medium driven by Saccharomyces cerevisiae α-factor signal sequence. From the initial screening, PpbX1, PpbG2 and PpbS1 recombinants from strain X-33, GS115 and SMD1168, respectively, had the highest expression level of W200R protease. The expression of these recombinants was further optimized under by modifying several parameters such as media composition, concentration of methanol, aeration and induction time. The protease activities detected from these three recombinants were 87.65 U/ml for PpbX1, 98.71 U/ml for PpbG2 and 147.5 U/ml for PpbS1. The W200R protease from PpbS1 recombinant was purified to 11.8 fold with 64% yield using heat-treatment method. The optimum temperature for the activity of this protease was 70 ºC and was stable up to 85 ºC. The enzyme was stable in the pH range of 7.0 to10 with optimum pH of 8.0.